1988
DOI: 10.1145/50087.50089
|View full text |Cite
|
Sign up to set email alerts
|

A field study of the software design process for large systems

Abstract: The problems of designing large software systems were studied through interviewing personnel from 17 large projects. A layered behavioral model is used to analyze how three of these problems—the thin spread of application domain knowledge, fluctuating and conflicting requirements, and communication bottlenecks and breakdowns—affected software productivity and quality through their impact on cognitive, social, and organizational processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
953
1
12

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,590 publications
(1,033 citation statements)
references
References 28 publications
20
953
1
12
Order By: Relevance
“…Getting the requirements right, and dealing with unstable requirements, are notoriously difficult problems (e.g., [19]). By "requirements" in this case, I mean not just end user requirements, but anything that specifies what a team should deliver.…”
Section: Eliciting Communicating Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Getting the requirements right, and dealing with unstable requirements, are notoriously difficult problems (e.g., [19]). By "requirements" in this case, I mean not just end user requirements, but anything that specifies what a team should deliver.…”
Section: Eliciting Communicating Requirementsmentioning
confidence: 99%
“…For effective requirements engineering in GSD, we need to tackle additional issues that take on increased urgency. In particular, we need significantly to improve our ability to support the ongoing negotiation processes that are prevalent throughout the project lifecycle [19,23]. Negotiation is much more difficult in a GSD context, because of the diversity of backgrounds, communication problems, and the difficulty of responding to change [21].…”
Section: Research Challengesmentioning
confidence: 99%
“…The researchers observe and interpret the actions and beliefs of practitioners and the practitioners do not take active part in the research process. Most of the empirical literature on systems development is based on practice studies (e.g., Aaen et al 991;Bansler and B0dker 1993;Benbasat, Dexter, and Mantha 1980;Boehm and Papaccio 1988;Boland and Day 1982;Ciborra and Lanzara 1994;Curtis, Krasner, and Iscoe 1988;Elam et al 1987;Gould and Lewis 1985;Kozar 1993;Krasner, Curtis, and Iscoe 1987;Madabusyhi, Jones and Price 1993;Markus 1983;McKeen 1983;Necco, Gordon, and Tsai 1987;Stolterman 1992;Tan 1994;Waltz, Elam, and Curtis 1993;White 1984;White and Leifer 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Sambamurthy and Kirsch (2000) identified seven core concepts in ISD literature -tasks (of the development team including planning, analysis, design), stakeholders, agenda (stakeholders' goals), transactions (stakeholder actions), context (outside of the stakeholders and team), structure (e.g., SDMs, tools, policies) and outcomes. Similarly, Curtis (1988) proposed a "layered development model", which gives the possible units of analysis for studying ISD, including "individual", "team", "project", "company" and "business milieu". Meanwhile, Bansler (1989) organized ( …”
Section: Sci and Isd Literaturementioning
confidence: 99%
“…Developing large systems involves communication, learning and negotiation processes (Curtis et al 1988 While knowledge is often defined as true, justified belief, Orlikowski (2002) found that "knowing is not a static embedded capability or stable disposition of actors, but rather an ongoing social accomplishment, constituted and reconstituted as actors engage the world in practice" (p. 250).…”
Section: Interpersonal Interactions In Isdmentioning
confidence: 99%